Utilization of Online Accounting Software As A Supplier Data Collection System At The Company - Sudaryono​, Sudaryono​; Aisyah, Euis Siti Nur; Keat​, Ooi Yeng (APTISI Transactions on Management (ATM), 2017)
Practical data collection system and has a very good security needed by small companies and large companies because the development of a company is a success in storing and controlling data well. In the company there will definitely be suppliers for the smooth running of business or the undertakings of the business undertaken, with conditions like this company should not be mistaken in storing and controlling data suppliers so then needed online accounting software developed as a place for supplier data collection system that provides facilities to make new suppliers, add suppliers with import features, change / delete / archive supplier list and record the beginning balance of online debt that does not complicate the user. The purpose of this study is to direct the company to do a good inventory data collection. The research method used is field research techniques so that the system made to meet the needs of the company so the system created to facilitate the company in managing information suppliers owned. Keywords: ​Practical data ​Supplier , ​Online Accounting Software, Company.